Patterns of hip flexion motion predict frontal and transverse plane knee torques during a single-leg land-and-cut maneuver - Kippa, K.; McLeanb, S. G.; Palmieri-Smit, R. M. (Clinical Biomechanics, 2011)
Impulsive frontal plane knee joint torques directly strain the anterior cruciate ligament and therefore may contribute to injury risk. Because deleterious torques may in part be related to aberrant kinematic movement patterns the primary purpose of this study was to establish a prediction model for frontal plane knee joint torques based on motion characteristics derived from Principal Component Analysis. Methods